The perceptions of construction workers on designing a workplace nutrition intervention in the UK. (20th October 2021) - Wronska, M; Coffey, M; Robins, A
Abstract:  : According to the European Commission, construction is an important industry providing the EU with 18 million jobs and contributing to 9% of the EU's GDP in 2020. Construction workers struggle with healthy food choices due to lack of knowledge, long working hours, remote site locations, poor food facilities on site, and temporary accommodation. Yet, nutrition interventions in construction are rare, with no UK studies. This is an exploratory study designed to investigate workers' perceptions of a workplace intervention to facilitate healthy nutrition choices. Engaging participants in the intervention design showed positive results on behaviour change. Five internally homogenous focus groups were conducted on three different construction sites (in three companies); two with managers (n = 11) and three with workers (including subcontractors) (n = 27). Sites differed in size (14; 50-100; and 300 workers); two were temporary. Framework Analysis was used to analyse data. The main themes uncovered in the focus groups were; 1) the need for workers to learn about food to sustain good energy levels, as deemed crucial for their job 2) the desire to get an understanding about portion sizes, food labels, impacts of food on mood and practical ideas of healthy snacks and meal planning and 3) the importance of intervention accessibility for everybody on site (including subcontractors), convenient scheduling and location, and managers support to encourage participation. A participatory approach was used to explore workers' suggestions on the content and delivery of the nutrition intervention. Education and practicality of recommendations were of the essence to workers, who suggested that individual characteristics, the nature of construction jobs (e.g. busy schedules, transient jobs), and resources available (e.g. storage) need to be considered when designing the intervention. Inclusivity, accessibility and managerial support were regarded as valuable in the intervention delivery. Key messages: This research produced recommendations to encourage the development and implementation of inclusive nutrition interventions in construction, to improve the health and wellbeing of workers. This research invites public health consultants and senior leaders in construction to invest in supporting healthy behaviours of workers, with a consideration of job and workplace characteristics.